PEDOGOGICAL DESCRIPTION OF THE ACTIVITIES OF A ROWING SPORTS COACH - Mamajonova, Sevara (Science technology&Digital finance, 2023)
This article provides information about the activities of the rowing sports coach, the administrative – economic functions of the coach, the reputation of the coach, the rules governing the activities of the coach.